The Relationship Between Digital Health Literacy and Treatment Compliance in Patients with Non-Communicable Diseases - Rifahatul Mahmudah (Stikes Syedza Saintika Padang, 2025)
Non-communicable diseases (NCDs) are a global challenge, accounting for more than 70% of deaths, particularly in developing countries (WHO, 2020). Medication adherence plays an important role in preventing complications, yet remains low due to limited access and understanding of health information (Basu et al., 2020). This study aimed to determine the relationship between Digital Health Literacy (DHL) and medication adherence among NCD patients in the working area of Kuranji Primary Health Center. This research used a quantitative method with a descriptive-analytic design and a cross-sectional approach. The population consisted of all NCD patients in the working area of Kuranji Primary Health Center, with a sample of 51 patients selected through accidental sampling. The results showed that out of 51 respondents, 33 (64.7%) had high digital health literacy and 30 (58.8%) demonstrated high medication adherence. The chi-square test revealed a p-value of 0.000 (p ≤ 0.05), indicating a significant relationship between digital health literacy and medication adherence among NCD patients at Kuranji Primary Health Center. It can be concluded that improving DHL supports patient adherence. Therefore, health workers at Kuranji Primary Health Center are recommended to optimize digital health literacy education for NCD patients.